2014
DOI: 10.1136/tobaccocontrol-2014-051717
|View full text |Cite
|
Sign up to set email alerts
|

Secondhand smoke emission levels in waterpipe cafes in Doha, Qatar

Abstract: Elevated levels of particulate pollution were found in waterpipe cafes in Doha, Qatar, potentially endangering the health of employees and patrons. To protect the public from the dangers of secondhand tobacco smoke, and to change social norms around tobacco use, smoke-free policies that apply to all forms of combusted tobacco products, including the waterpipe, are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 28 publications
0
22
1
Order By: Relevance
“…Recent studies from the Middle East region that used comparable study designs to ours have documented similarly elevated levels of one to two orders of magnitude in venues such as waterpipe cafes compared to those where tobacco smoking was banned. 16,19,20 In contrast, other studies have reported differences between venues that were slightly smaller than those in our study. For example, recent air monitoring in seven cities in the United States found PM 2.5 to be 82% lower in smoke-free hospitality settings than in venues where smoking was permitted.…”
Section: Discussioncontrasting
confidence: 99%
“…Recent studies from the Middle East region that used comparable study designs to ours have documented similarly elevated levels of one to two orders of magnitude in venues such as waterpipe cafes compared to those where tobacco smoking was banned. 16,19,20 In contrast, other studies have reported differences between venues that were slightly smaller than those in our study. For example, recent air monitoring in seven cities in the United States found PM 2.5 to be 82% lower in smoke-free hospitality settings than in venues where smoking was permitted.…”
Section: Discussioncontrasting
confidence: 99%
“…We did not identify many significant associations between venue characteristics and SHS levels. Other studies of SHS in waterpipe tobacco venues have reported positive associations between smoker density and mean PM 2.5 (Abuelaish et al, 2013; Al Mulla et al, 2014; Cobb et al, 2013; Saade et al, 2010; Zaidi et al, 2011; Zhang et al, 2013). …”
Section: Discussionmentioning
confidence: 82%
“…Environmental Protection Agency, 2013; World Health Organization, 2014). Other studies of waterpipe tobacco venues in the US (Cobb et al, 2013; Fiala et al, 2012; Zhang et al, 2013; Zhou et al, 2014), Qatar (Al Mulla et al, 2014), Lebanon (Saade et al, 2010), Pakistan (Zaidi et al, 2011), and Palestine (Abuelaish et al, 2013) have all found elevated PM 2.5 concentrations, with mean concentrations ranging from 117 μg/m 3 to 1,419 μg/m 3 .…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Lando et al 4 report on successful practices and communication strategies to adopt a comprehensive ban on smoking aboard US submarines. Al Mulla et al 5 and Zhou et al remind us not to forget that non-cigarette products that are burned, like waterpipe, can quickly pollute the air just like cigarettes and at levels the US Environmental Protection Agency would classify as ‘hazardous’ if it were measured outdoors. This is particularly important because some smoke-free policies have loopholes that make enforcement of these policies problematic when it comes to waterpipe smoking.…”
mentioning
confidence: 99%